A potência da quadratura e a pujança da Perspectiva na Lisboa Joanina - Moraes Mello, Magno (Linguagens nas artes, 2022)
Resumo: O estudo propõe analisar a pintura perspéctica em Portugal no período que corresponde aos séculos XVII e XVIII. Esta abordagem enfatiza a relação da história da Ciência com a História da Artes atraves do estudo da produção dos tratados manuscritos ou impressos, será possível explicar melhor não só o papel fundamental da elite intelectual da época, como também o conhecimento de uma verdadeira postura teórica em relação a quadratura na perspectiva de Joanina. Nesse sentido, busca-se refletir sobre a arte decorativa e perspectica de São Vicente de Fora em Portugal. Palavra chave: Tratados; Arte de perspectiva; Arte decorativa; Saõ Vicente de Fora; Século XVIII. Abstract: The study proposes to analyze perspective painting in Portugal in the period corresponding to the 17th and 18th centuries. This approach emphasizes the relationship between the history of Science and the History of the Arts through the study of the production of manuscripts or printed treatises, it will be possible to better explain not only the fundamental role of the intellectual elite of the time, but also the knowledge of a true theoretical posture in relation to the square in Joanina’s perspective. In this sense, we seek to reflect on the decorative art and perspective of São Vicente de Fora in Portugal. Keywords: Treaties; Perspective art; Decorative art; Sao Vicente de Fora; XVIII century. Recebido em: 03/09/2021 – Aceito em 30/09/2021 <span style="color: #202124; font-family: Roboto, ’Helvetica Neue’, Arial, sans-serif; font-size: 20px; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: 28px; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none; background-color: #ffffff;">